2001
DOI: 10.1046/j.0953-816x.2001.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and noradrenaline efflux in the rat prefrontal cortex after classical aversive conditioning to an auditory cue

Abstract: We used bilateral microdialysis in the medial prefrontal cortex (PFC) of awake, freely moving rats to study aversive conditioning to an auditory cue in the controlled environment of the Skinner box. The presentation of the explicit conditioned stimuli (CS), previously associated with foot shocks, caused increased dopamine (DA) and noradrenaline (NA) efflux. This conditioned response was dependent on the immediate pairing of the two stimuli; in the pseudoconditioned group that received an equal number of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 32 publications
5
53
1
Order By: Relevance
“…This response pattern well agrees with preferential excitations of presumed DA neurons induced by arousing somato-sensory stimuli in awake animals, as shown both in the SNc (Freeman et al, 1985;Freeman and Bunney, 1987;Steinfels et al, 1983;Strecker et al, 1985;Schultz, 1986;Trulson, 1985) and VTA (Guarraci and Kapp, 1999;Freeman and Bunney, 1987;Kiyatkin, 1988;Horvitz et al, 1997;Schultz, 1986). These data are also consistent with large body of neurochemical data (DA metabolism, [DA] evaluated by microdialysis or electrochemistry) suggesting increased DA release, especially in cortical projections, associated with arousing and aversive stimulation (Abercrombie et al, 1989;Deutch et al, 1985;Fadda et al, 1978;Feenstra et al, 2000Feenstra et al, , 2001Kiyatkin, 1995;Le Moal and Simon, 1991;Thierry et al, 1976). It appears that this response is typical to the awake conditions when sensory effects and activation mechanisms are intact and functional; somatosensory-evoked discharges typical to most striatal neurons were greatly eliminated during general anesthesia (see Kiyatkin and Brown, 2007;West, 1996).…”
Section: Sensory Responses Of Ls and Ss Vta Neuronssupporting
confidence: 85%
“…This response pattern well agrees with preferential excitations of presumed DA neurons induced by arousing somato-sensory stimuli in awake animals, as shown both in the SNc (Freeman et al, 1985;Freeman and Bunney, 1987;Steinfels et al, 1983;Strecker et al, 1985;Schultz, 1986;Trulson, 1985) and VTA (Guarraci and Kapp, 1999;Freeman and Bunney, 1987;Kiyatkin, 1988;Horvitz et al, 1997;Schultz, 1986). These data are also consistent with large body of neurochemical data (DA metabolism, [DA] evaluated by microdialysis or electrochemistry) suggesting increased DA release, especially in cortical projections, associated with arousing and aversive stimulation (Abercrombie et al, 1989;Deutch et al, 1985;Fadda et al, 1978;Feenstra et al, 2000Feenstra et al, , 2001Kiyatkin, 1995;Le Moal and Simon, 1991;Thierry et al, 1976). It appears that this response is typical to the awake conditions when sensory effects and activation mechanisms are intact and functional; somatosensory-evoked discharges typical to most striatal neurons were greatly eliminated during general anesthesia (see Kiyatkin and Brown, 2007;West, 1996).…”
Section: Sensory Responses Of Ls and Ss Vta Neuronssupporting
confidence: 85%
“…Rats were trained in a fully controlled environment (Skinner box) to associate a neutral auditory stimulus with the receipt of an unconditioned stimulus. Applying this approach, we reported that presentation of aversive conditioned stimuli increased both prefrontal NA and DA in vivo efflux (Feenstra et al, 2001), indicating a role for both catecholamines in coding the significance value of stimuli. Therefore, we tested the hypothesis that presentation of appetitive conditioned stimuli would also lead to activation of both catecholamine afferents to the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…GBR increases extracellular dopamine, which in turn generates reactive oxygen species (ROS) (39,40) in regions richly innervated by dopaminergic terminals, such as the ACC. This pharmacological approach partially mimics the pronounced prefrontal dopamine release during psychosocial stress (41,42).…”
Section: Sixmentioning
confidence: 99%